Correction: Enantiomeric NMR discrimination of carboxylic acids using actinomycin D as a chiral solvating agent. Issue 15 (28th March 2019) - Bai, Liwen; Chen, Pian; Xiang, Jiangxia; Sun, Jiarui; Lei, Xinxiang
Abstract : Correction for 'Enantiomeric NMR discrimination of carboxylic acids using actinomycin D as a chiral solvating agent' by Liwen Bai, et al., Org. Biomol. Chem., 2019, 17, 1466–1470.